Classics in total synthesis III : further targets, strategies, methods - Nicolaou, K. C.; Chen, J. S. (Wiley-VCH ; John Wiley [distributor], 2011)
Excellent explanations of all key steps of the synthetic pathway. This makes the book a wonderful tool for learning and teaching organic chemistry Well-designed graphics and two colours throughout Target molecules are all natural products with interesting properties - special importance for pharmaceutical industry K.C.